Effectiveness of periodontal therapy on target HBA1C achievement of type2-diabetic patients with periodontits from public primary care clinics in Kuantan - Tin, Myo Han; Md Aris, Mohd Aznan; Ismail, Razida; Yaacob, Munirah; Osman, Iskandar Firzada; Sidek, Sorayah; Thuraiapprah, Mahendran; Abdullah, Fa’iza; Hari, Padmini; Than, Tun Sein; Saub, Roslan (2017)
Diabetes mellitus (DM) patients who achieved treatment target HbA1c ≤ 6.5% was 17.4% in Malaysia. Prevalence of DM patients with periodontitis co-morbidity (DM-P) in Malaysia was 53.3%. Effectiveness of non-surgical periodontal therapy (NSPT) on glycemic control of DM-P patients has been reported in previous studies.